Social licences to operate: For better not for worse; for richer not for poorer? The impacts of unplanned mining closure for 'fence line' residential communities. - Browne, A.; Stehlik, Daniela; Buckley, Amma (Routledge, 2011)
Establishing "social licencs to operate" with communities has become a significant corporate social responsibility agenda. The complex dynamics of these relationships can compound the impacts for communities when these contracts are not upheld. This article documents reflections from a rapid rural appraisal conducted in the Shire of Ravensthorpe in remote Western Australia after the Ravensthorpe Nickel Operation was "mothballed" 9 months into a projected 25-year lifespan. It captures how communication about the project and its time frames created a sense of consistency, predictability, certainty and trust - enabling social licence. The raising of hope and the emergence of mistrust underpin social, environmental and financial impacts of this event for the local community. Embedded in the theoretical dimensions of social licences, this case study highlights the problematic of social licences that engage with non-contractual stakeholders as partners in "booms" but have no legal responsibility towards them in times of "bust".